INTERAKSI SIMBOLIK USTADZ-SANTRI (STUDI FENOMENOLOGI PADA PONDOK PESANTREN DAR EL HIKMAH PEKANBARU) - Andi Kardian Riva’i (Ensiklopedia of Journal, 2020)
This study aims to determine the symbolic interaction of Ustadz-Santri at the Dar El Hikmah Islamic Boarding School in Pekanbaru. The assumption of the concept of symbolic interaction explains that humans form meaning through the process of communication. what we want to see in this study is the extent to which symbolic ustadz and santri interactions are formed from the self-concept and perceptions of each individual based on their interactions. The results that can be seen from this study are, that symbolic interaction in Islamic boarding schools, especially the Dar El Hikmah Islamic Boarding School in Pekanbaru, is not only seen from the learning process that makes humans (santri) able to understand and know science, but more than that symbolic ustadz-santri at the Dar El Hikmah Islamic boarding school in Pekanbaru is the process of developing attitudes, mentality and behavior. therefore the symbolic interaction inherent in Ustadz with santri with all its dynamics is educated, able to know, able to act according to the responsibilities of the santri who are characterized by Faith and Faith (IMTAQ) and Science and Technology (Science and Technology), the result of a intensive and long enough to influence and motivate thinking and the establishment of a positive relationship between Ustadz and santri is the relationship of father and son closeness, and symbolic meanings that occur in the Dar El Hikmah boarding school formed from the tradition of the hut tarting from daily activities such as eating, praying in congregation in mosques, recitation of the book of salaf, formal schools to weekly activities such as scouting and Muhadlaroh (public speaking).